The Irishman's daughter [large type] - Alexander, V. S. (Kennebec Large Print superior collection., 2019)
"Ireland, 1845. To Briana Walsh, no place on earth is more beautiful than Carrowteige, County Mayo, with its sloping fields and rocky cliffs perched above the wild Atlantic. The small farms that surround the centuries-old Lear House are managed by her father, agent to the wealthy, reckless Sir Thomas Blakely. Tenant farmers sell the oats and rye they grow to pay rent to Sir Thomas, surviving on the potatoes that flourish in the remaining scraps of land. But when the potato crop falls prey to a devastating blight, families Briana has known all her life are left with no food, no resources, and no mercy from the English landowner, who seems indifferent to everything except profit. Rory Caulfield, the hard-working young farmer Briana hopes to marry, shares the locals' despair--and their anger. There's talk of violent reprisals against the callous gentry and their agents. Briana's studious older sister, Lucinda, dreams of a future far beyond Mayo. But even as hunger and disease settle over the country, killing and displacing millions, Briana knows she must find a way to guide her family through one of Ireland's darkest hours--toward hope, love, and a new beginning"--